Overcoming Resistance of Human Non-Hodgkin’s Lymphoma to CD19-CAR CTL Therapy by Celecoxib and Histone Deacetylase Inhibitors - Torres-Collado, Antoni Xavier (Cancers (Basel), 2018)
Patients with B-cell non-Hodgkin’s lymphoma (B-NHL) who fail to respond to first-line treatment regimens or develop resistance, exhibit poor prognosis. This signifies the need to develop alternative treatment strategies. CD19-chimeric antigen receptor (CAR) T cell-redirected immunotherapy is an attractive and novel option, which has shown encouraging outcomes in phase I clinical trials of relapsed/refractory NHL. However, the underlying mechanisms of, and approaches to overcome, acquired anti-CD19CAR CD8(+) T cells (CTL)-resistance in NHL remain elusive. CD19CAR transduced primary human CTLs kill CD19(+) human NHLs in a CD19- and caspase-dependent manner, mainly via the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) apoptotic pathway. To understand the dynamics of the development of resistance, we analyzed several anti-CD19CAR CTL-resistant NHL sublines (R-NHL) derived by serial exposure of sensitive parental lines to excessive numbers of anti-CD19CAR CTLs followed by a limiting dilution analysis. The R-NHLs retained surface CD19 expression and were efficiently recognized by CD19CAR CTLs. However, R-NHLs developed cross-resistance to CD19CAR transduced human primary CTLs and the Jurkat human T cell line, activated Jurkat, and lymphokine activated killer (LAK) cells, suggesting the acquisition of resistance is independent of CD19-loss and might be due to aberrant apoptotic machinery. We hypothesize that the R-NHL refractoriness to CD19CAR CTL killing could be partially rescued by small molecule sensitizers with apoptotic-gene regulatory effects. Chromatin modifiers and Celecoxib partially reversed the resistance of R-NHL cells to the cytotoxic effects of anti-CD19CAR CTLs and rhTRAIL. These in vitro results, though they require further examination, may provide a rational biological basis for combination treatment in the management of CD19CAR CTL-based therapy of NHL.